Retrospective review of children with vertigo: a 3-year experience - Korkmaz, Muhammet Furkan; Ekici, Arzu (The European Research Journal, 2020)
Objectives: To evaluate the age, sex, accompanying symptoms, etiologic factors and laboratory findings in children with vertigo in a tertiary research hospital. Methods: A total of 183 children (65 boys and 118 girls), aged 3-18 (median:14), who presented with complaints of vertigo between November 2016 and September 2019 in the pediatric neurology department were examined retrospectively. Systemic and neurological examination findings, laboratory findings including complete blood count and biochemical tests (fasting blood glucose, electrolytes, liver-kidney function tests), iron, iron-binding capacity, ferritin, vitamin B12 level and thyroid function test results, electroencephalography (EEG) and magnetic resonance imaging findings were examined. Results: The frequency of vertigo complaints were found to be higher in female gender (p = 0.008). The frequency of admission was significantly higher in adolescents (> 12 years) (67%) compared to other age groups (p < 0.001). The most common cause of vertigo was benign paroxysmal vertigo of childhood (BPVC) (23%) and orthostatic hypotension (22%) was the second. When the relationship between the etiology of vertigo and age was examined, the most common cause was BPVC under 12 years of age, where as orthostatic hypotension was significantly more frequent in adolescents (p < 0.001). Headache (41%), syncope (27%) and nausea-vomiting (10%) were the most common accompanying symptoms with vertigo. Epileptiform disorder was detected in 7% of patients who underwent EEG. Of 171 patients who underwent neuroimaging, 85% reported as normal and 10% had non-specific findings. Conclusions: In children presenting with a complaint of vertigo, a detailed history including the age at when the complaint began and the accompanying symptoms, physical examination, blood pressure measurement, laboratory tests, and EEG and neuroimaging (if necessary) should be performed with a multidisciplinary approach.